2008 1st IFIP Wireless Days 2008
DOI: 10.1109/wd.2008.4812886
|View full text |Cite
|
Sign up to set email alerts
|

Codec-based adaptive QoS control for VoWLAN with differentiated services

Abstract: Voice over Wireless LAN (VoWLAN) is becoming more and more helpful in our life and is expected to be among the most important applications in next generation networks. However, the maximum number of VoIP sessions that a WLAN can ensure is very small. Moreover, when the WLAN reaches its capacity the addition of one VoIP session affects the QoS parameters of all VoIP sessions. In this paper, we propose an adaptive technique to ensure the active VoIP sessions of users with high priority (from a provider perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Therefore, we defined the capacity for VoIP as the maximum number of wireless nodes so that both uplink and downlink delay do not exceed 60 ms. Moreover, as shown in our previous works [4,23], the uplink delay added less than 1 ms of transmission delay, which allows us to assume that the end-to-end delay is essentially the same as the downlink delay. We also defined the capacity for VoIP as the maximum number of wireless nodes so that the jitter delay did not exceed 10 ms, and therefore, the MOS did not fall below 3.6.…”
Section: Performance Evaluation Of Vowlan Servicesmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, we defined the capacity for VoIP as the maximum number of wireless nodes so that both uplink and downlink delay do not exceed 60 ms. Moreover, as shown in our previous works [4,23], the uplink delay added less than 1 ms of transmission delay, which allows us to assume that the end-to-end delay is essentially the same as the downlink delay. We also defined the capacity for VoIP as the maximum number of wireless nodes so that the jitter delay did not exceed 10 ms, and therefore, the MOS did not fall below 3.6.…”
Section: Performance Evaluation Of Vowlan Servicesmentioning
confidence: 86%
“…One of the most problematic unsolved issue concerning VoWLANs is bandwidth inef f iciency [1][2][3]. For instance, ten calls with the G.729 codec can hardly be supported on 802.11b with acceptable quality of service (QoS), even without competing traffic-less than 2% efficiency [4]. Furthermore, when the WLAN reaches its capacity, the addition of one VoIP call does not only affect its own QoS parameters (delay, packet loss, .…”
Section: Introductionmentioning
confidence: 99%
“…Tebbani and Haddadou [12] have investigated congestion of voice communication over wireless LANs and have proposed an adaptive technique of selecting compressed codecs for lower priority calls. This adaptive technique factors in user priorities and current wireless LAN congestion.…”
Section: B Related Workmentioning
confidence: 99%
“…The proposed schemes in [12]- [15] are focused on resolving the types of errors and packet losses exhibited by wireless networks and do not consider the services that can be provided by WANs and MPLS networks.…”
Section: B Related Workmentioning
confidence: 99%
“…A similar research undertaking in[7] has shown that VolP capacity measured in simulations and test beds can given similar results, provided limitation in the two methods are addressed appropriately. Increasing VolP capacity on wireless LAN, by changing CODEC, is researched in[8] and[9]. Using buffering to enhance…”
mentioning
confidence: 99%